2020
DOI: 10.1109/access.2020.3035720
|View full text |Cite
|
Sign up to set email alerts
|

A Deep-Learning-Based Method for Solving Nonlinear Singular Lane-Emden Type Equation

Abstract: The nonlinear Lane-Emden type equation can be used to describe many physical phenomena. To solve this type of equation, a method based on deep neural network is proposed. The output layer of this network has two layers, the last one of which scaling the outputs of their neighbors with an aim at coping with issues where the values of function to be approximated are much less or larger than the order of 1. The Lane-Emden equation and its initial conditions are employed to construct the loss function, and the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In other words, a hybrid data loss function is used. Other options exist like solving an equivalent system of two first-order differential equations instead of a single second order one, as for a standard analytical approach (He et al, 2020). Nevertheless, as shown by our results, our method is efficient.…”
Section: Our Pinn Algorithmmentioning
confidence: 87%
See 1 more Smart Citation
“…In other words, a hybrid data loss function is used. Other options exist like solving an equivalent system of two first-order differential equations instead of a single second order one, as for a standard analytical approach (He et al, 2020). Nevertheless, as shown by our results, our method is efficient.…”
Section: Our Pinn Algorithmmentioning
confidence: 87%
“…Some methods are analytical ones, numerical ones, or combinations of both. A rather complete summary of the various approaches can be found in He et al (2020). Classical numerical methods including the traditional Runge-Kutta methods have to circumvent the singularity problem, by using some transformation, Taylor-like expansion, or avoiding the origin.…”
Section: Introductionmentioning
confidence: 99%
“…By analysing the application of fair value in financial accounting, it can be found that the application of fair value in the process of financial accounting is based on the enterprise actual economic situation; Furthermore it helps enterprise decision-makers with financial report issued by the financial and accounting controls over a period of enterprise economics to take decisions, helps to make accurate projections for enterprise development and also the direction, strengthens the work level and ability of enterprise financial accounting and helps to realise the transformation of enterprise financial accounting to management accounting [7]. From the traditional way of enterprise financial accounting work, it will be very difficult for the decision makers to know the real financial information and the risks involved in real-time and moreover it will take certain time to realise that.…”
Section: Introductionmentioning
confidence: 99%